Why Are Jobs Designed the Way They Are? - Cindy Zoghi; Alec Levenson; Michael Gibbs (Institute for the Study of Labor (IZA), 2005)
In this paper we study job design. Will an organization plan precisely how the job is to be done ex ante, or ask workers to determine the process as they go? We first model this decision and predict complementarity between these job attributes: multitasking, discretion, skills, and interdependence of tasks. We argue that characteristics of the firm and industry (e.g., product and technology, organizational change) can explain observed patterns and trends in job design. We then use novel data on these job attributes to examine these issues. As predicted, job designs tend to be ?coherent? across these characteristics within the same job. Job designs also tend to follow similar patterns across jobs in the same firm, and especially in the same establishment: when one job is optimized ex ante, others are more likely to be also. There is some evidence that firms may segregate different types of job designs across different establishments.
Keywords: J2; M50; L23; M5; J24; 330; job design; organization design; specialization; job enrichment; intrinsic motivation; Anforderungsprofil; Berufsbegleitende Ausbildung; Organisatorischer Wandel; Theorie